1997
DOI: 10.1021/la970615i
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Methanol on ZSM-5 Zeolites

Abstract: The interaction of methanol with a NaZSM-5 and a HZSM-5 zeolite was investigated by means of temperature-programmed desorption (TPD) and adsorption measurements. For both zeolites the desorption curves are structured, indicating different adsorption sites. In the case of HZSM-5 the desorption at higher temperatures is accompanied with a partial conversion of methanol. It was investigated how the course of the reaction depends on the initial adsorbed amount of methanol. Using a regularization method, desorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 50 publications
6
39
0
Order By: Relevance
“…Higher values of activation energies of desorption of DME than methanol are generally in accordance with previous studies [40,[52][53][54][55] but in contrast to values obtained by Pope [56] through calorimetric methods (Table 5). …”
Section: Comparing Desorption Of Methanol To Dmesupporting
confidence: 92%
“…Higher values of activation energies of desorption of DME than methanol are generally in accordance with previous studies [40,[52][53][54][55] but in contrast to values obtained by Pope [56] through calorimetric methods (Table 5). …”
Section: Comparing Desorption Of Methanol To Dmesupporting
confidence: 92%
“…Indeed, Hunger et al. observed that methanol has a stronger affinity for the ZSM‐5 surface than water, citing the presence of the CH 3 group as a possible reason for this . The CH 3 OH that is retained forms coke more efficiently and lowers the mass balance of the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The desorption of hydrogen, methane, ethylene, methanol, C3 + hydrocarbons, and DME were monitored by m/e = 2, 16, 27, 31, 43, and 45, respectively. Desorbed methanol was detected mostly below 200 °C, indicating an operating condition in which methanol conversion had not completed and side reaction should be suppressed [32]. DME was observed in the range from 150 °C to 300 °C, a so-called pre-inition phase of methanol conversion [33], which can be used to interpret the bonding strength of the Brønsted acid [32].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, aromatic molecules are subsequently formed via the hydride transfer of olefin precursors [36]; therefore, the trend of hydride mobility may be considered as the indication of the aromatization Desorbed methanol was detected mostly below 200 • C, indicating an operating condition in which methanol conversion had not completed and side reaction should be suppressed [32]. DME was observed in the range from 150 • C to 300 • C, a so-called pre-inition phase of methanol conversion [33], which can be used to interpret the bonding strength of the Brønsted acid [32]. The desorption peak of DME increased with the following trend: HZ-D (230 • C) < HZ (249 • C) < HZ-DA (256 • C), in line with the Brønsted acidity observed from NH 3 -TPD.…”
Section: Resultsmentioning
confidence: 99%